(untitled) (The Review of Diabetic Studies, 2025)
Background: High-alert medications pose a significant risk of patient harm when mismanaged, particularly in Emergency Departments (EDs), where time-sensitive decisions and high workload increase the likelihood of medication errors. Clinical pharmacists and emergency nurses play critical and complementary roles in mitigating these risks through dose verification, medication preparation, administration, and patient monitoring. However, the extent of their collaboration and its impact on medication safety outcomes remain insufficiently explored. Aim: This systematic review aims to synthesize current evidence on the roles of clinical pharmacists and emergency nurses in managing high-alert medications within EDs, and to examine how interprofessional collaboration influences medication safety and workflow efficiency. Methods: Following PRISMA 2020 guidelines, a comprehensive search was conducted across PubMed, Scopus, Web of Science, CINAHL, and Google Scholar for studies published between 2010 and 2025. Eighteen studies met the inclusion criteria and were analyzed through narrative synthesis. Quality appraisal was performed using the Newcastle–Ottawa Scale, CASP, and JBI tools.